Changes with time after feeding in ruminal pool sizes of cellular contents, crude protein, cellulose, hemicellulose and lignin - FADEL EL-SEED, A N M A; SEKINE, J; KAMEL, H E M; HISHINUMA, HISHINUMA (The Indian Journal of Animal Sciences, 2014)
The rate and extent of contribution by particle frations to the total pool size reduction were evaluated for the digesta pools in the rumen of 16 nature Sheep uning a slaughter method. Orchard grass first-cut hay ehoppcd to:2 ern was offered once a day @ 1.5% of live weight. After 7-day preliminary period, behaviour of achive prehension and rumination was recorded for 24 hr. Four animals were Hlaughtered at 2,8, IG and 24 hr after feed offered. digesta in the rumen was divided into 4 fractions remaining particles on sieves with apertures of 1.18 (LP). 0.30 (MP) and 0.045 mm (MP), and fine particles passed through sitwe with aperture of 0.045 mm (FPL). Orchard grass hay coutaincd 83 g/kg DM of crude protein (CP), 728 g/kg DM of neutral detergent fibre, 447 glkg aM of acid detcrgent fibre, and 67 g/kg DM of acid detergent lignin (ADL). Mean dry-mailer (DM) intake by sheep was 320Â±85 g/2 hr period, mean quantity of ruminal contents was 6.0+-1.4 kg on as is basis, and 560Â±185 g on DM basis. Pool sizes of DM and other nutrients in the rumen were significantly decreased with the time elapsed after feeding (P